TANGGUNGJAWAB SYAHBANDAR DALAM PELAKSANAAN TUGASNYA SEBAGAI PENGAWAS KESELAMATAN PELAYARAN - Rahman, Abdul (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT.The role of Syahbandar needs to be improved through nautical, technical and administrative skills as well as work discipline, increased dedication to task development in order to realize the safety of ships, goods and lives at sea. This study examines the form of syahbandar's responsibility for shipping safety based on applicable laws and efforts that can be made to increase the effectiveness of syahbandar's responsibility in maintaining shipping safety. Using normative research, in this case, normative legal research is a process to find legal rules, legal principles, and legal doctrines to answer the legal problems raised, using a legislative approach. Syahbandar plays a vital role in ensuring shipping safety, which is regulated by a number of regulations, such as Law No. 17 of 2008 concerning Shipping and its derivative regulations. The responsibilities of the syahbandar include ship feasibility inspections, issuance of Sailing Approval Letters, cargo supervision, and safety education, and a series of efforts that modernization, syahbandar include technology improvement of competence, harmonization of regulations, inter agency coordination, and increased safety awareness..Keywords: Syahbandar, Shipping Safety..